ANALISIS PENGARUH GONCANGAN FAKTOR EKSTERNAL TERHADAP PERTUMBUHAN EKONOMI - Monica Wulandari; Hasdi Aimon; Mike Triani (Universitas Negeri Padang, 2017)
The purpose of this research is to see how far the influence of external factors toward the economic growth in Indonesia and also to see any external factors that can decreasing economic growth in short and long term. The method is used in this research is Ordinary Least Square with use Error Correction Model (ECM) test and Cointegration. Based on analysis data was obtained three conclusions were; The first is based on the results of multiple regression, foreign investment and world oil prices and a significant positive effect on economic growth in Indonesia, while the exchange rate and foreign debt and no significant positive effect on economic growth in Indonesia at the 5% significance level. The second is in the short term through the Error Correction Model (ECM) test, the world oil price and foreign direct investment to boost economic growth while exchange rate USD / (NTR) and External Debt (ED) can shocks the economic growth in Indonesia. The third is in the long term through cointegration test, the variables included in the model and no significant negative effect on economic growth